ELEMENTOS HISTÓRICOS SOBRE LA PROSTITUCIÓN FEMENINA EN COSTA RICA. EL CASO DEL VALLE CENTRAL NOROCCIDENTAL - Fernández Carballo, Rodolfo (2005)
In this article the reader will find a social-historical analysis on several aspects that evidence feminine prostitution in the Northwestern Section of the Costa Rican Central Valley during the XX Century. To this end, we have carried out an in-depth valuation regarding the diverse social factors that gave rise to this phenomenon in the region, without excluding other localities in the country that in one way or the other are linked to the area under study. Based on diverse sources and recent investigations and, naturally, on personal testimonies, we intend to reconstruct an activity that was —and continues to be— forged by the different social players of past and present Costa Rica.